(untitled) (American Journal of Islam and Society, 2011)
The media play a contributing influence in exacerbating hostilities between war protagonists. Through particular representations, specific groups are either hailed or vilified; thereby resulting in a “spill-over effect” of negative stereotyping, prejudice, and hostilities among people beyond the physically-designated zones of conflict. The 2006 Israeli-Hezbollah War, fueled by Israel’s history of military aggression in the region and ignited by Hezbollah’s cross-border raid into Israel and the associated capture and killing of Israeli soldiers, received extensive coverage in the South African press and had the effect of polarizing groups in support of a particular side. In this article, we examine a section of the local South African print media—capturing the conflict to reveal the main discourse themes, their hidden ideological positions and their legitimation through specific textual devices. The findings reveal a “discursive war” between news texts representing a favorable stance on Israel and Hezbollah respectively. Through characterizations and intertextual practices, (“right of existence” and “defense against terror” versus “religious resistance” and “Israel as the apartheid state” respectively) that provided legitimation for violence. The ideological effects of such media representations on the ordinary lives of South Africans physically removed from the conflict are considered. In light of the findings, considerations for discursive interventions are proposed in order to promote discourses of peace in the media.